The Short Story “I Want My Son to Become a Murderer“ in Deconstructive Analysis - Siti Hafsah (Ethical Lingua: Journal of Language Teaching and Literature, 2019)
Deconstruction in short story "I Want My Son to Become a Murderer" shows a binary opposition which leads into an understanding that there is no hierarchy opposition. Derrida deconstruction in literary work aims to show logical and rhetorical non-equivalence between what explicitly written and what is implicitly hidden in the text. The deconstruction study shows how the contradictions should be uncovered from the text which called dissemination. The result of the analysis shows the opposition found are: (1) opposition between title and story; (2) opposition between the story and the footnote; (3) opposition between intuitive comprehension and logical reasoning; (4) opposition between fact and fiction; (5) opposition between “I lyric” and many people; and (6) opposition between the writer and the reader.